The Role of Aspergillus Antibody Detection in Allergic Bronchopulmonary Aspergillosis - Aqidatul Islamiyyati Elqowiyya; Anna Rozaliyani (Green Publisher Indonesia, 2024)
Allergic bronchopulmonary aspergillosis (ABPA) is an allergic lung disorder characterized by an exaggerated immune response to fungal allergens, particularly from Aspergillus fumigatus. ABPA leads to excessive mucus production and impaired mucociliary clearance. When A. fumigatus conidia are inhaled, they germinate, release exoproteases and other substances that further impede mucociliary clearance, and activate the immune response. The immune response is known by an exaggerated Th2 response to Aspergillus antigens, leading to production of IgE antibodies, eosinophilic infiltration of the lungs, and the formation of immune complexes. These immune complexes can deposit in the lung tissue, leading to airway inflammation, bronchiectasis, and fibrosis. This disease mainly occurs in individuals diagnosed with bronchial asthma and cystic fibrosis. Increased levels of A. fumigatus total IgE and specific IgE, IgG, and IgA antibodies, play a role in diagnosing patients with ABPA.